Peningkatan Literasi Digital pada Anak Usia Dini dalam Merekontruksi Moral Menuju Pendidikan Berkualitas Perspektif SDGS 2030 - Muhammad Fikri Ramdhani; Bagus Satria Pratama; Ichsan Fauzi Rachmat (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The purpose of writing this article is to explore how character education can support the achievement of the Sustainable Development Goals, especially in the context of the quality of education in Indonesia. The type of research used in this article is qualitative research, using descriptive-critical analysis that emphasizes the analysis of data obtained through various sources of books and other writings. The results show that character education is an important aspect in improving the success of education. Because the big challenge in the education system is the biggest factor in the low quality of education in Indonesia. So it is necessary to make more active efforts to develop the character education of the nation's children so that the role of the SDGs program can be carried out and its goals are in line with efforts to equalize education, and become a reference and impetus to further encourage the character education of Indonesian citizens.